PENHANCING ARTS CREATIVITY THROUGH BATIK ACTIVITIES (HERITAGE EDUCATION BUILDS EARLY CHILDREN CHARACTER) - Mardhatillah Mardhatillah (SENSEI RESEARCH CENTER, 2021)
This research aims to obtain empirical data regarding the activity of making batik in an effort to increase the artistic creativity of group B students of Permata Hati Kindergarten. The method used in this study was classroom action research. In this study the researcher acted as a teacher in batik activities, and the class teacher acted as a collaborator and observator. This research went through four stages of activity, namely planning, action, observation and reflection. The research action was carried out in two cycles with a total of 12 meetings. The data sources in this study were Group B students of Permata Hati Kindergarten. Data collection was carried out through rubrics, observations, interviews, and documentation studies. The results of the study show that batik activities can increase children's artistic creativity, which in the pre-cycle was recorded at 31%. Then it increased to 56.50% at the end of the first cycle and continued to increase to 83.70% at the end of the second cycle. This shows that the research target of at least 80% has been achieved. The results of the study concluded that batik is a good alternative method for increasing early childhood artistic creativity.